The Dow Jones-Irwin dictionary of financial planning - Richards, Robert William (Homewood, Ill. : Dow Jones-Irwin, 1986)
This reference is designed to be an important source of terms to help alleviate problems caused by the volatile and broad-range characteristics of financial planning. It contains over 3,000 entries and is intended to be used by professionals and lay persons alike. All users can benefit from the quick-referencing subject index as well as the comprehensive dictionary format.
Includes index.
ne 09/09/2021
Ref.
Keywords: Finance